SMART GARBAGE ALERT SYSTEM USING MACHINE LEARNING - Mr. M. Imayavaramban, Dr. V. Devarajan, Aravindhan R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Now a day, Waste management is one of the primary problem that the world faces irrespective of the case of developed or developing country. The key issue in the waste management is that the garbage bin at public places gets overflowed well in advance before the commencement of the next cleaning process. It leads to various hazards such as bad odour & amp; ugliness to that place which may cause for spread of various diseases. To avoid all such hazardous scenario and maintain public cleanliness and health our project is mounted on a smart garbage system. The main aim project is to develop a smart intelligent garbage alert system for a proper garbage management. The main aim project is to develop a smart intelligent garbage alert system for a proper garbage management. Our project proposes a smart AI dustbin which is Collect the Real time dataset of what’s in the Garbage and Classify the Waste. Prepare the Dataset for an Image classification. Train the Neural Network and Create a Tensor Flow Model and Deploy the Model. After it is also interfaced with hardware using ultrasonic sensor. The sensor values are read and the values are displayed in the LCD. Hence, garbage management is done by using both image processing and embedded system. Based on the image processing output, the respective degradable and non-degradable dustbins are opened by showing relay operations.